2015
DOI: 10.1056/nejmoa1414266
|View full text |Cite|
|
Sign up to set email alerts
|

Follow-up of Glycemic Control and Cardiovascular Outcomes in Type 2 Diabetes

Abstract: After nearly 10 years of follow-up, patients with type 2 diabetes who had been randomly assigned to intensive glucose control for 5.6 years had 8.6 fewer major cardiovascular events per 1000 person-years than those assigned to standard therapy, but no improvement was seen in the rate of overall survival. (Funded by the VA Cooperative Studies Program and others; VADT ClinicalTrials.gov number, NCT00032487.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
342
2
13

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 582 publications
(364 citation statements)
references
References 22 publications
7
342
2
13
Order By: Relevance
“…In a recent ACCORD substudy examining the relationship between glycaemic control and CV risk, a consistent reduction of CV events associated with better glycaemic control was reported 20. The VADT study reported a non‐significant 12% reduction in the risk of a MACE+ outcome (which differed in components from that in CREDIT) associated with a 1.5% reduction in HbA1c 2, a finding that became significant with a 17% reduction in events at 10 years in the extension phase 21. The ADVANCE study saw a 6% non‐significant reduction in MACE events associated with a 0.8% reduction in HbA1c 4.…”
Section: Discussionmentioning
confidence: 91%
“…In a recent ACCORD substudy examining the relationship between glycaemic control and CV risk, a consistent reduction of CV events associated with better glycaemic control was reported 20. The VADT study reported a non‐significant 12% reduction in the risk of a MACE+ outcome (which differed in components from that in CREDIT) associated with a 1.5% reduction in HbA1c 2, a finding that became significant with a 17% reduction in events at 10 years in the extension phase 21. The ADVANCE study saw a 6% non‐significant reduction in MACE events associated with a 0.8% reduction in HbA1c 4.…”
Section: Discussionmentioning
confidence: 91%
“…2,37 The few favorable demonstrations of reduced rates of cardiovascular events with predominantly glucose-lowering therapies have required more protracted follow-up than routinely occurs in clinical trials. 4,7 Although our study had only approximately 2 years of follow-up, sufficient numbers of cardiovascular events were observed so that we could reasonably exclude a major nonglycemic cardiovascular benefit 21 as well as an unanticipated harm of lixisenatide.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a major risk factor for development of cardiovascular diseases (2). In patients with diabetic nephropathy, appropriate management of blood glucose level is important to delay the progression to end-stage renal disease and prevent the development of cardiovascular disease (3,4). Although many kinds of hypoglycemic agents are currently available for the management of blood glucose level, most agents cannot be used in patients with advanced-stage diabetic nephropathy because decreased renal function delays their elimination from the body, leading to adverse effects.…”
Section: Introductionmentioning
confidence: 99%